2006
DOI: 10.1300/j069v25n04_09
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of a National Sample of Qualified Addiction Specialists Who Have and Have Not Prescribed Buprenorphine for Opioid Dependence

Abstract: The limited availability of medication-assisted treatment has created a treatment gap leaving many opioid dependent individuals without access to appropriate treatment. Survey data from a national random sample of 545 addictions physicians with waivers to provide buprenorphine treatment under The Drug Addiction Treatment Act of 2000 are presented. During the first year, an estimated 63,204 opioid dependent patients were treated with buprenorphine; many were dependent on prescription opioids and were new to dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
96
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 25 publications
7
96
1
Order By: Relevance
“…Despite the fact that methadone maintenance treatment slots are available for only 20% of the 1.7 million opioiddependent Americans, 12,13 physicians have been slow to prescribe buprenorphine for opioid addiction treatment. 14 In one study of addiction specialist physicians (who had buprenorphine waivers), only 58% had ever prescribed buprenorphine, and one quarter of them reported that they reduced or discontinued prescribing it. 14 There are a number of potential reasons for this slow uptake at both the health care system and physician-level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that methadone maintenance treatment slots are available for only 20% of the 1.7 million opioiddependent Americans, 12,13 physicians have been slow to prescribe buprenorphine for opioid addiction treatment. 14 In one study of addiction specialist physicians (who had buprenorphine waivers), only 58% had ever prescribed buprenorphine, and one quarter of them reported that they reduced or discontinued prescribing it. 14 There are a number of potential reasons for this slow uptake at both the health care system and physician-level.…”
Section: Introductionmentioning
confidence: 99%
“…14 In one study of addiction specialist physicians (who had buprenorphine waivers), only 58% had ever prescribed buprenorphine, and one quarter of them reported that they reduced or discontinued prescribing it. 14 There are a number of potential reasons for this slow uptake at both the health care system and physician-level. The Drug Addiction Treatment Act of 2000 requires physicians who prescribe buprenorphine to obtain a waiver and obtain a special X number from the Drug Enforcement Agency (DEA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information regarding buprenorphine waivers is maintained in the Drug Enforcement Agency's Controlled Substances Act (CSA) Registrants database. In the fi rst year after FDA approval, about 2,000 physicians applied for the buprenorphine waiver (Kissin et al, 2006), which had increased to more than 20,000 physicians holding the waiver by 2011 (Stein et al, 2015).…”
mentioning
confidence: 99%
“…Considerable work has examined its diffusion in SUD treatment programs and OTPs (Brigham et al, 2007;Ducharme & Abraham, 2008;Ducharme et al, 2007;Friedmann et al, 2010;Gordon et al, 2007;Knudsen et al, 2006Knudsen et al, , 2009Koch et al, 2006;Kovas et al, 2007;Wallack et al, 2010). Several surveys of physicians have examined the nexus between attitudes and prescribing (Arfken et al, 2010;Kissin et al, 2006;Netherland et al, 2009;Reif et al, 2007;Thomas et al, 2008;WESTAT, 2006).…”
mentioning
confidence: 99%